2018
DOI: 10.1136/jech-2018-210675
|View full text |Cite
|
Sign up to set email alerts
|

Childhood IQ and mortality during 53 years’ follow-up of Swedish men and women

Abstract: Lower IQ was associated with an increased risk of mortality in men and women. The explanatory effects of socioeconomic factors in adulthood suggest that they constitute an important pathway in the association between IQ and mortality, especially in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…In the SVMR analysis, we found that CP reduces the risk for attempting suicide by almost 30%; however, after incorporating EA and income into a MVMR framework, CP was no longer associated with suicidal behavior, which supports previous observational literature finding that EA explains a substantial proportion of the association between CP and suicidal behavior 80 82 . CP and EA are genetically correlated 37 , and there is MR evidence supporting a bidirectional relationship between EA and CP 73 ; however, using MVMR methods and sensitivity analyses to assess for possible pleiotropy, we were able to extricate their independent effects on the risk for having attempted suicide, which is critical when considering policies aimed at preventing suicide.…”
Section: Discussionsupporting
confidence: 84%
“…In the SVMR analysis, we found that CP reduces the risk for attempting suicide by almost 30%; however, after incorporating EA and income into a MVMR framework, CP was no longer associated with suicidal behavior, which supports previous observational literature finding that EA explains a substantial proportion of the association between CP and suicidal behavior 80 82 . CP and EA are genetically correlated 37 , and there is MR evidence supporting a bidirectional relationship between EA and CP 73 ; however, using MVMR methods and sensitivity analyses to assess for possible pleiotropy, we were able to extricate their independent effects on the risk for having attempted suicide, which is critical when considering policies aimed at preventing suicide.…”
Section: Discussionsupporting
confidence: 84%
“…Notably, in our single-variable MR analysis, we found that CP reduces the risk for attempting suicide by almost 30%; however, after incorporating EA and income into a MVMR framework, CP was no longer significantly associated with suicidal behavior, which supports previous observational literature finding that EA explains a substantial proportion of the association between CP and suicidal behavior [60][61][62]. CP and EA are genetically correlated [36], and there is MR evidence supporting a bi-directional relationship between EA and CP [54]; however, using multivariable MR methods and sensitivity analyses to assess for possible pleiotropy, we were able to extricate their direct effects on the risk for having attempted suicide, which is critical when considering policies aimed at preventing suicide.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, one possible reason for the long-term association between intelligence and suicidal behavior is that intelligence is robustly associated with attained education and socioeconomic position in adulthood (Plomin and Deary, 2015). These factors have been found to explain substantial proportions of the association between intelligence in youth and suicidal behavior in adulthood (Sörberg et al ., 2013; Sörberg Wallin et al ., 2018 a ). They may be relevant to prevention at the societal level, not least because socioeconomic factors contribute considerably to suicide risk at the population level (Li et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…They may be relevant to prevention at the societal level, not least because socioeconomic factors contribute considerably to suicide risk at the population level (Li et al ., 2011). Of note is that this pathway might be more important for suicide prevention in men than in women; in women, low intelligence seems to be associated with suicide attempt (Sörberg Wallin et al ., 2018 b ) but not death from suicide (Andersson et al ., 2008; Calvin et al ., 2017; Sörberg Wallin et al ., 2018 a ). The fact that gender differences are observed in these relationships further supports the hypothesis that social and socioeconomic factors are involved as mediators or moderators in the associations.…”
Section: Discussionmentioning
confidence: 99%